Analisis Beban Kerja Petugas Filling Rekam Medis Rawat Jalan dengan Metode WISN di RSU Haji Surabaya Tahun 2020 - Nur Hasanah Ayu Purnamawati; Novita Nuraini; Yuni Astuti (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Surabaya Haij General Hospital is one of the type B educational hospitals that has stored medical record files in the filling room. Surabaya Hajj General Hospital has 37 Outpatient Clinics with the number of visits in 2020 is 93,232 patients with an average number of old patient visits per day is 890.14 patients and the average number of new patient visits per day is 42.18 patients (Haji Hospital Surabaya, 2018) with 95.48% of old patients to the total number of outpatient visits. Outpatient filling is obtained that there are still a lot of outpatient medical records file that have been scattered or not yet entered on the filling rack. The purpose of this study is to analyze the workload of outpatient filling staff with the Work Load Indicator Staff Need (WISN) method at RSU Haji Surabaya in 2020. This research uses descriptive research type, with the method of observation and interview of 6 outpatient medical records filling officers. The object of this study is the workload of medical records filling officers. The results showed that the calculation of available working time for outpatient filling staff was 113,100 minutes / year, the main activities of outpatient filling staff at RSU Haji Surabaya were 44 minutes, Standard workload for outpatient filling officers at RSU Haji Suarabaya was 49,952 files / year, Standard allowance for outpatient filling staff at Surabaya Haji Hospital is 0.195 hours / year, with the results of the WISN calculation is 8 officers and a WISN ratio of 19.6.